1986-87 edition of the Annuaire Biographique de la Francophonie - Quito, Emerita S. (Animo Repository, 1986)
Philosophy Department Chairperson Emerita Quito was included in the 1986-87 edition of the Annuaire Biographique de la Francophonie (Biographical Directory of French-speakers) published by the Cercle Richelieu de Paris, Agence de Cooperation Culturelle et Technique, and Nathan